Liver disease with unknown etiology - have you ruled out alpha-1 antitrypsin deficiency? - Dhiren Patel; Jeffrey Teckman (SAGE Publishing, 2021)
Although a less well-known consequence of alpha-1 antitrypsin deficiency (AATD) liver disease is the second leading cause of death among patients with the condition. The alpha-1 antitrypsin (AAT) protein is produced by hepatocytes within the liver, which retain pathological variants of AAT instead of secreting the proteinase inhibitor into the systemic circulation. This intracellular retention is caused by inefficient folding and polymerization of mutant AAT and the accumulation of these AAT aggregates leads to diverse manifestations of liver disease, which can present differently in both children and adults. The progression from hepatocyte apoptosis to liver inflammation, fibrosis and cirrhosis, and liver failure is still not fully understood, but in older patients, liver disease can surpass lung disease as the principal cause of death. Liver function tests (LFTs) can measure plasma levels of liver enzymes to assess liver function but require careful interpretation. Non-invasive tests are being developed that can detect early liver disease, but liver biopsy is still the gold standard for assessing liver fibrosis once abnormal LFTs have been detected in a patient. Currently, there is no licensed treatment for AATD-related liver disease (intravenous AAT therapy is not indicated for this purpose), but liver transplantation is associated with positive outcomes and may even slow emphysema progression. Therefore, new strategies are being developed to address treatment of AATD-related liver disease, such as accelerating degradation of mutant AAT and assisting hepatocytes in the folding and secretion of mutant AAT, but these approaches remain at early stages of development.